BIMBINGAN PADA REMAJA DALAM UPAYA MENINGKATKAN KEMATANGAN KARIR BERBASIS LIFE SKILLS - Erfian Syah (Jurnal Bimbingan Penyuluhan Islam, 2022)
Adolescence is a very important phase in the life cycle of an individual development, as it leads to healthy adults. This period shows clearly transition from childhood to adulthood. Very One of the problems that arise at this stage is career problems. Becomea logical consequence of adolescent development where there are demands for those who are preparing for a career Career problems that occur in adolescents are usually related to educational choices, leading to elections type of work in the future, this issue is very important to pay attention to related to the many experiences experienced by adolescents in determining majors from his career,To meet the career needs of adolescents, assistance is needed intensive training of professionals such as counselors in providing guidance and counseling services, a needs assessment needs to be linked Today's demands, the main curriculum of life skills-based education (life skills), which have become a fundamental problem of youth, necessary for life skill-based career guidance in an effort to increase career maturity.